Exogenous Galectin-9 prevents peri-implantitis in rats by regulating macrophage polarization - Cheng, Lujin; Ji, Xiaowei; Yilihamujiang, Huerxidai; Dong, Shuya; Mei, Long; Lin, Guo; Tang, Qihan; Gong, Zhongcheng (Frontiers in Pharmacology, 2025)
BackgroundPeri-implantitis (PI) is a common complication of oral implants with no definitive treatment strategy. Lipopolysaccharides (LPS) are involved in PI by activating macrophages and influencing osteoclasts and osteoblasts. Galactin-9 (Gal-9) is known for its immunomodulatory properties and interactions with macrophage polarization receptors. This study investigated the mechanism of prophylactic exogenous Gal-9 in the prevention and treatment of PI in rats.MethodsMale SD rats with titanium implants were divided into the Control, Saline, and Gal-9 groups. Rats in the Saline group and Gal-9 group were prophylactically administered Gal-9 and Saline, respectively, before inducing PI. Periodontal examinations, X-ray imaging, flow cytometry analyses, and micro-CT evaluations were conducted to assess clinical, imaging, and immunological parameters.ResultsAfter inducing PI, the implant loss rate in the Gal-9 group was lower than that in the Saline group. The gingival index was higher in the Saline group and Gal-9 group compared to the Control group. The bleeding on probing positivity rate was higher in the Saline group than in the other two groups. X-ray and micro-CT images both showed lower alveolar bone resorption in the Gal-9 group than in the Saline group. Flow cytometry showed that the proportions of M1-type macrophages and M2-type macrophages, and M1/M2 ratio were lower in the Gal-9 group than those in the Saline group. Multivariate linear regression indicated that Tb.Th had the greatest impact on the gingival index and Tb.Sp had the greatest impact on the M1/M2 ratio.ConclusionExogenous Gal-9 administration demonstrated promising effects in mitigating inflammation associated with PI in rat models by promoting M2 macrophage polarization and enhancing alveolar bone stability.